Ocean Acidification Affects Volatile Infochemicals Production and Perception in Fauna and Flora Associated With Posidonia oceanica (L.) Delile - Mutalipassi, Mirko; Mazzella, Valerio; Schott, Matthias; Fink, Patrick; Glaviano, Francesca; Porzio, Lucia; Lorenti, Maurizio; Buia, Maria Cristina; von Elert, Eric; Zupo, Valerio (Frontiers in Marine Science, 2022)
Communication among marine organisms are generally based on production, transmission, and interpretation of chemical cues. Volatile organic compounds (VOCs) can act as infochemicals, and ocean acidification can alter their production in the source organisms as well as the interpretation of the information they drive to target organisms. Two diatoms (Cocconeis scutellum var. parva and Diploneis sp.) and a macroalga (Ulva prolifera), all common epiphytes of Posidonia oceanica leaves, were isolated and cultured at two pH conditions (8.2 and 7.7). Their biomass was collected, and the VOCs produced upon wounding were extracted and analyzed using gas chromatography. Chemotactic reactions of invertebrates triggered by VOCs were tested using a static choice experimental arena and a flow-through flume system. Odor choice experiments were performed on several invertebrates associated with P. oceanica meadows to investigate the modification of behavioral responses due to the growth of algae in acidified environments. Complex patterns of behavioral responses were recorded after exposure to algal VOCs. This study demonstrated that a) ocean acidification alters the bouquet of VOCs released by diatoms and macroalgae and b) these compounds act as infochemicals and trigger peculiar behavioral responses in benthic invertebrates. In addition, behavioral responses are species-specific, dose-dependent, and are modified by environmental constraints. In fact, the static diffusion in choice arenas produced different responses as compared to flow-through flume systems. In conclusion, we demonstrate that in future marine environments higher CO2 concentrations (leading to a pH 7.7 by the end of this century) will modify the production of VOCs by micro- and macroalgae as well as the recognition of these infochemicals by marine invertebrates.